Considerate, convivial and capacious? Finding a language to capture ethos in 'creative' schools. Issue 6 (2nd November 2017) - Bragg, Sara; Manchester, Helen
ABSTRACT: Concepts of school 'ethos' or 'culture' have been widely debated in education since the 1980s. This is partly as a consequence of marketisation, partly because ethos has been identified as a low-cost route to school improvement. Corporate, authoritarian, and most recently 'military' models of ethos have been widely promulgated in the UK. Another significant strand of educational thinking, however, has emphasised ethos for and as learning: how schools might prefigure alternative, more socially just, worlds. This article argues that accounting for such divergent notions of ethos demands greater attention to the intellectual resources mobilised in interpreting educational processes. We discuss schools that used their work with the English creative learning programme, Creative Partnerships, to develop what we describe as 'considerate, convivial and capacious' school ethos. We aim thereby to value their achievements, provide tools to contest dominant discourses around ethos, and advocate more critical, reflexive approaches to researching school cultures.